PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. RATIO CONSTRUCTION - I G. A. Agung Prasiska Dewi (Majalah Ilmiah Widyacakra, 2019)
The Influence of Workload and Work Stress On Employee Work Productivity at CV. Ratio Construction. The success of management in managing the company will be largely determined by the ability in processing and utilizing the human resources, but without realizing by the company, many employees get stress due to overload of workload and this will have an impact on reducing the employee work productivity. This research aimed to analyze the influence of the workload and work stress on employee work productivity at CV. Ratio Construction. The sample of this research is 35 respondents of employees CV. Ratio Construction. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the workload and work stress influenced on employee work productivity is 54,3%, based on hypothesis testing with the F and t test results, it can be concluded that the workload variable (X1) and work stress (X2) simultaneously (together} and significantly influence on employee work productivity variable (Y) with value of F-test is 18, 983 and sig 0,000. The workload variable (X1) partially and significantly positive influenced on employee work productivity variable (Y) with value of t-test is 5,940 and sig. 0,000 and work stress variable (X2) significantly negative influenced on employee work productivity variable (Y) with value of t-test is -2,366 and sig. 0,024.